2021
DOI: 10.1101/2021.03.03.433740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lack ofTgfbr1andAcvr1bsynergistically stimulates myofibre hypertrophy and accelerates muscle regeneration

Abstract: TGF-β, myostatin and activin A are involved in regulation of muscle mass and contribute to the progressive pathology of muscle wasting disorders by regulating muscle fibrosis and inhibiting satellite cell proliferation and differentiation. Inhibition of TGF-β signalling through knockout of TGF-β type I receptors Tgfbr1 and Acvr1b may be a promising therapeutic approach. Here we show how muscle morphology and early muscle regeneration are altered in a myofibre specific knockout of Tgfbr1 and/or Acvr1b. Simultan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 114 publications
(176 reference statements)
0
1
0
Order By: Relevance
“…In addition to the largest number of DEGs, double knockout of TGF-β type I receptors induced the largest hypertrophy in fast-type muscle. Previously we have shown that 5 weeks after tamoxifen-induced knockout of both TGF-β type I receptors in skeletal muscle, type IIB myofibre CSA of tibialis anterior muscle was increased by twofold, while type I myofibre CSA was not changed 52 . Here, three months after inducible knockout of both type I receptors, FCSA was increased in both fast-and slow-type muscles.…”
Section: Discussionmentioning
confidence: 82%
“…In addition to the largest number of DEGs, double knockout of TGF-β type I receptors induced the largest hypertrophy in fast-type muscle. Previously we have shown that 5 weeks after tamoxifen-induced knockout of both TGF-β type I receptors in skeletal muscle, type IIB myofibre CSA of tibialis anterior muscle was increased by twofold, while type I myofibre CSA was not changed 52 . Here, three months after inducible knockout of both type I receptors, FCSA was increased in both fast-and slow-type muscles.…”
Section: Discussionmentioning
confidence: 82%